Modulation of MKNK2 alternative splicing by splice-switching oligonucleotides as a novel approach for glioblastoma treatment. Issue 21 (17th October 2018) - Mogilevsky, Maxim; Shimshon, Odelia; Kumar, Saran; Mogilevsky, Adi; Keshet, Eli; Yavin, Eylon; Heyd, Florian; Karni, Rotem
Abstract: The gene encoding the kinase Mnk2 ( MKNK2 ) is alternatively spliced to produce two isoforms—Mnk2a and Mnk2b. We previously showed that Mnk2a is downregulated in several types of cancer and acts as a tumor suppressor by activation of the p38–MAPK stress pathway, inducing apoptosis. Moreover, Mnk2a overexpression suppressed Ras-induced transformation in culture and in vivo . In contrast, the Mnk2b isoform acts as a pro-oncogenic factor. In this study, we designed modified-RNA antisense oligonucleotides and screened for those that specifically induce a strong switch in alternative splicing of the MKNK2 gene (splice switching oligonucleotides or SSOs), elevating the tumor suppressive isoform Mnk2a at the expense of the pro-oncogenic isoform Mnk2b. Induction of Mnk2a by SSOs in glioblastoma cells activated the p38–MAPK pathway, inhibited the oncogenic properties of the cells, re-sensitized the cells to chemotherapy and inhibited glioblastoma development in vivo . Moreover, inhibition of p38–MAPK partially rescued glioblastoma cells suggesting that most of the anti-oncogenic activity of the SSO is mediated by activation of this pathway. These results suggest that manipulation of MKNK2 alternative splicing by SSOs is a novel approach to inhibit glioblastoma tumorigenesis.